Violet Biology and Management in Turf - Darcy E. P. Telenko; Barry J. Brecke; Ramon Leon; J. Bryan Unruh (EDIS)
Violets (Viola spp.) are diverse winter annuals and perennials. Perennials form rhizomes or long stolons. Many have heart-shaped leaves on long petioles and have a rosette growth habit. Some have linear leaves and others have palmate leaves. Flowers are generally purple, but can be white, pink or yellow. They reproduce by seed or, when produced, rhizomes. This 2-page fact sheet was written by Darcy E. P. Telenko, Barry J. Brecke, Ramon Leon, and J. Bryan Unruh, and published by the UF Department of Environmental Horticulture, December 2013.